The impact of income generated by business activities and operational costs on the net profit for the period spanning from 2019 to 2022 - Dewi, Herlina Puspa (Universitas Wiralodra, 2023)
business income and operational expenses on net profit in food and beverage sub-sector companies listed on the Indonesian Stock Exchange (BEI) in 2019-2022. The sample in this research was 15 companies over 4 years. The sampling technique uses the purposive sampling method. The analytical method used is descriptive analysis and regression analysis with normality test. Multicollinearity test, heteroscedasticity test, and autocorrelation test, and the research design used is quantitative correlation. The results of this research show that simultaneously, variable operating income and operational expenses have a significant effect on net profit. Partial test results show that the operating income variable has a significant positive effect on net profit. However, the operational expense variable does not have a significant positive effect on net profit.